Neurodevelopmental benefits of judo training in preschool children: a multinational, mixed methods follow-up study - Križalkovičová, Zuzana; Szabó, Péter; Kumli, Kata; Štefanovský, Miloš; Makai, Alexandra; Szentpéteri, József (Frontiers in Psychology, 2024)
In our quasi-experimental study, we evaluated the neurodevelopmental impact of judo on young children (n = 182) aged 4–7 years, specifically focusing on primitive reflex integration. Participants were divided into judo and non-judo control groups, and assessments were conducted over six months across Hungary, Slovakia, and Austria. Neurodevelopmental changes were measured using INPP (Institute for Neuro-Physiological Psychology) and PANESS (Physical and Neurological Examination for Soft Signs) for children, while parents completed the PSQ (Performance Skills Questionnaire). Analysis with Repeated Measures ANOVA (significance set at p<0.05) revealed significant improvements in cognitive and motor performance in judo-practicing children compared to their non-judo counterparts. Furthermore, Spearman correlation analysis revealed that INPP and PANESS were effective in identifying neurodevelopmental changes, PSQ was not suitable as a simplified screening tool for parents, potentially due to its absence of items focused on primitive reflexes. Despite the limitations of the study, our findings suggest that judo practice could foster central nervous system (CNS) maturation in young children, promoting the potential inclusion of judo in early childhood education programs.